1999
DOI: 10.1002/(sici)1097-0231(19991215)13:23<2348::aid-rcm797>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

On-line high-performance liquid chromatography/mass spectrometric investigation of amyloid-β peptide variants found in Alzheimer's disease

Abstract: Abeta peptides are the major components of amyloid deposits in Alzheimer's disease. The presence of N-terminally truncated Abeta variants in amyloid may be a critical factor in Alzheimer's disease pathogenesis. These Abeta variants are less soluble and more amyloidogenic than full-length Abeta, making their separation, purification and identification difficult. High-performance liquid chromatography (HPLC) at elevated temperatures, coupled to electrospray ionization (ES) mass spectrometry (MS), enables rapid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Many techniques and protocols were developed to increase the sensitivity to different forms of A␤, especially the A␤ pE peptides (34,35). Equipped with a set of novel antibodies, Saido et al (15) showed by immunohistochemical and biochemical means that A␤ pE3 is present in equivalent or larger amounts than full-length A␤ in senile plaques.…”
Section: Discovery Of Pyroglutamate A␤mentioning
confidence: 99%
“…Many techniques and protocols were developed to increase the sensitivity to different forms of A␤, especially the A␤ pE peptides (34,35). Equipped with a set of novel antibodies, Saido et al (15) showed by immunohistochemical and biochemical means that A␤ pE3 is present in equivalent or larger amounts than full-length A␤ in senile plaques.…”
Section: Discovery Of Pyroglutamate A␤mentioning
confidence: 99%
“…Peptide aggregation and the presence of these modifications could potentially confound immunoassay‐based procedures. There have been a number of reports on the use of mass spectrometry (MS) for the analysis of A β peptides 17–32. These studies have generally either focused on structural aspects of A β ‐peptides or the analysis of cell‐derived peptides 23.…”
Section: Reported Concentrations Of Aβ1‐42 In Human Csfmentioning
confidence: 99%
“…It has been demonstrated that the amyloid‐β‐peptides are neurotoxic 2, 3. The development of amyloid fibrils, which are internal parts of senile plaques, is connected with the concentration and the size of the amyloid‐β‐peptides 4–7…”
Section: Introductionmentioning
confidence: 99%